2018
DOI: 10.5194/hess-22-3841-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of young water fractions to hydro-climatic forcing and landscape properties across 22 Swiss catchments

Abstract: Abstract. The young water fraction F yw , defined as the proportion of catchment outflow younger than approximately 2-3 months, can be estimated directly from the amplitudes of seasonal cycles of stable water isotopes in precipitation and streamflow. Thus, F yw may be a useful metric in catchment inter-comparison studies that investigate landscape and hydro-climatic controls on streamflow generation. Here, we explore how F yw varies with catchment characteristics and climatic forcing, using an extensive isotop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
217
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(240 citation statements)
references
References 41 publications
17
217
6
Order By: Relevance
“…They found that an increase in annual rainfall amounts of 1 mm d −1 led to an increase of 0.03-0.04 in the modeled Fyw (percentage point increase of 3 %-4 %, hereafter written as 0.03-0.04, where the value 1 means that 100 % of streamflow is younger than 3 months). Similar to this, von Freyberg et al (2018) found a positive correlation between Fyw and high-intensity precipitation events. This dependence of Fyw on precipitation characteristics could lead to long-term changes in Fyw due to global warming.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…They found that an increase in annual rainfall amounts of 1 mm d −1 led to an increase of 0.03-0.04 in the modeled Fyw (percentage point increase of 3 %-4 %, hereafter written as 0.03-0.04, where the value 1 means that 100 % of streamflow is younger than 3 months). Similar to this, von Freyberg et al (2018) found a positive correlation between Fyw and high-intensity precipitation events. This dependence of Fyw on precipitation characteristics could lead to long-term changes in Fyw due to global warming.…”
supporting
confidence: 80%
“…Streamflow was substantially comprised of groundwater, as its volume-weighed δ 18 O was −8.40 ‰, the precipitation isotope signal was strongly attenuated in streamflow, and Fyw(189) values were generally low, which indicates a strong groundwater influence. The study by Weigand et al (2017) came to the same conclusion for the Wüstebach catchment using wavelet analysis of nitrate and DOC data collected at mainstream and tributary locations. While lower-altitude locations of the catchment near the outlet were dominated by groundwater, higher-altitude areas were less affected.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Agriculture, grassland, and forests are found at elevations up to approximately 2,000 m, above which the ground cover is mostly meadow (and some rock, snow, or ice). The effects of these catchment characteristics on streamflow transit times and runoff processes have been described in previous studies (Seeger & Weiler, 2014;von Freyberg et al, 2018).…”
Section: Catchment Characteristicsmentioning
confidence: 99%